2017
DOI: 10.18632/oncotarget.17228
|View full text |Cite
|
Sign up to set email alerts
|

Engineering a high-affinity humanized anti-CD24 antibody to target hepatocellular carcinoma by a novel CDR grafting design

Abstract: Cluster of differentiation 24 (CD24) is a specific surface marker involved in the tumorigenesis and progression of hepatocellular carcinoma (HCC). However, all reported anti-CD24 antibodies are murine ones with inevitable immunogenicity. To address this, a method using both molecular structure and docking-based complementarity determining region (CDR) grafting was employed for humanization. After xenogeneic CDR grafting into a human antibody, three types of canonical residues (in the VL/VH interface core, in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…Despite the low potency of doxorubicin (the IC50 is in the low micromolar range) compared to the active drugs in most ADCs, the ADC was still able to suppress tumour growth, decrease systemic toxicity, and prolong the survival of HCC-bearing nude mice [ 108 ]. A positive outcome for another ADC targeting CD24 has also been reported; the active drug was the previously discussed, more potent microtubule inhibitor, monomethyl auristatin E [ 109 ].…”
Section: Hepatocellular Carcinomamentioning
confidence: 99%
“…Despite the low potency of doxorubicin (the IC50 is in the low micromolar range) compared to the active drugs in most ADCs, the ADC was still able to suppress tumour growth, decrease systemic toxicity, and prolong the survival of HCC-bearing nude mice [ 108 ]. A positive outcome for another ADC targeting CD24 has also been reported; the active drug was the previously discussed, more potent microtubule inhibitor, monomethyl auristatin E [ 109 ].…”
Section: Hepatocellular Carcinomamentioning
confidence: 99%
“…By contrast, in patient-derived ovarian tumor samples, CD24-negative cells were more aggressive than CD24-positive cells, with stemness features and resistance to carboplatin and paclitaxel [172]. In hepatocellular carcinoma derived-xenografts, using a humanized monoclonal anti-CD24 antibody had anti-tumor effects, while there was no data on the eradication of the pool of cancer stem cells [173].…”
Section: Targeting Cancer Stem Cell Surface Markersmentioning
confidence: 99%
“…Subsequent studies identified specific antigen binding regions within the variable domains of the antibody called complementarity determining regions (CDRs). This development led to the ability to further reduce the immunogenicity of rodent‐derived antibodies by grafting only the CDRs and replacing the remaining framework regions (Fr) with the most homologous human sequences, resulting in the generation of humanized antibodies (Agadjanyan et al, ; Lo, ; Sun et al, ). It is generally recognized that even fully human mAbs can initiate a clinically relevant anti‐drug antibody response through the activation of CD4 + T cells and B cells (Baker & Jones, ; Harding, Stickler, Razo, & DuBridge, ).…”
Section: Introductionmentioning
confidence: 99%